(untitled) (Journal of Comparative & International Higher Education, 2024)
This study identifies three fundamental historical moments related to the incorporation of information and communication technologies in higher education. To explore these phases, we acknowledge an initial period defined by the massive use of computers, mostly for accounting and office automation; a second period during which highly specialized software emerges and expands its coverage in academic disciplines; and a third period characterized by a widespread use of Learning Management Systems and communication software during the COVID-19 pandemic.